Interferon and TLR genes, but not endogenous bornavirus-like elements, limit BoDV1 replication after intracerebral infection. - Rie Koide; Takaya Abe; Taichi Harimoto; Anselmo Jiro Kamada; Yuka Saito; Matteo Guerrini; Asami Fujii; Erica Parrish; Masayuki Horie; Hiroshi Kiyonari; Kazuhiko Yamamoto; Keizo Tomonaga; et al. (PLoS Pathogens)
Borna disease virus 1 (BoDV1) is a disease-causing agent in some livestock and, as has recently been shown, in humans. What constitutes a protective immune response to BoDV1 is unclear. Previous studies found that endogenous bornavirus-like nucleoprotein elements (EBLNs) present in mammalian genomes produce piRNAs antisense to BoDV1 nucleoprotein mRNAs. As a known function of piRNAs is to restrict transposons via RNA interference, it has been hypothesized that EBLN-derived piRNAs may restrict BoDV1. Here we used EBLN knockout (KO) and other KO mice to test genetic factors potentially involved in antiviral immunity to BoDV1. In previous reports, BoDV1 replication was higher in mice deficient in interferon gamma, and we confirmed a role for this cytokine in BoDV1 restriction at 12 weeks post infection using mice lacking its receptor. We show that BoDV1 replicates to higher levels in the brain of mice without Toll-like receptor 7 (TLR7), suggesting a role for this innate immune receptor in BoDV1 immunity. In contrast, mice lacking piRNA-producing EBLNs were no more susceptible to BoDV1 infection than wild-type under the infection conditions used here. We thus expand the genetic evidence implicating specific conventional immune pathways in BoDV1 control and conclude that EBLN-derived piRNA-guided antiviral silencing, if it occurs, is relatively less impactful in intracerebral infection of neonates.